Efficacy of Several Therapeutic Agents in a Murine Model of Dry Eye Syndrome - Kilic, Servet; Kulualp, Kadri (Amer Assoc Laboratory Animal Science, 2016)
In the current study, we used 56 female BALB/c mice with induced dry eye syndrome to evaluate the therapeutic effects of formal saline (FS), sodium hyaluronate (SH), diclofenac sodium (DS), olopatadine (OP), retinoic acid (RA), fluoromethanole (FML), cyclosporine A (CsA), and doxycycline hyclate (DH). All subjects were kept in an evaporative 'dry eye cabinet' for the assessment of blink rate, tear production, tear break-up time, and impression cytology prior to (baseline) and during weeks 2, 4, and 6 of the study. The right eyes of all subjects were treated topically with 5 AL of the test agent twice daily during weeks 2 through 6. Impression cytology and tear break-up time differed between time points in all groups and differed between groups at weeks 4 and 6. Blink rate differed by time point only in the FS, FML, and DH groups. Tear production according to the phenol red cotton thread test differed by time point for all groups except RA, CsA, and DH and differed between groups only at week 6. Among the compounds tested in the present study, DS and CsA were the most effective therapeutic agents in our mouse model of dry eye syndrome; these agents likely exert their therapeutic effect through their antiinflammatory activity.
Keywords: Ocular Surface; Antiinflammatory Therapy; Tear Production; Mouse Model; Topical Cyclosporine; Keratoconjunctivitis; Prevalence; Film; Sensitivity; Management